The Implementation of Autonomous Learning in Teaching Speaking for Senior High School Students at SMA N 3 Bantul - Diah Ayu Arditias; Nafisah Endahati (JEdu: Journal of English Education, 2022)
The aims of the research are to identify the implementation of autonomous learning in teaching speaking for senior high school students in SMA N 3 Bantul and to find out the factors that influence lack of speaking. The research was conducted in descriptive qualitative methodology. The data findings were obtained from the observation, interview and documentation of senior high school students of SMA N 3 Bantul. The participants of the research were the students of X IPA 1 of SMA N 3 Bantul. The data was divided into four points as follows: 1) the characteristic of autonomous learner, 2) the work-cycle of autonomous learning class, 3) teacher-students’ role in autonomous learning, 4) the factors that influence lack of speaking performance of senior high school students. The results of the research were categorized into two aspects. First it is the characteristics of autonomous language learner namely having high motivation, strong curiosity, aware to use technology, having the high self-confidence. The work-cycle of autonomous classroom were plan, do, and evaluate. Teacher- learner role in autonomous class consisted of teacher as facilitator, teacher as motivator and teacher as the resource and responsibility for making good environment of autonomous class.  Second, it is the factors that influence lack of speaking performance namely incorrect pronunciation, low grammar comprehension, low vocabulary mastery, low motivation, less self-confident, nervous and speaking anxiety, and lack of language input.